Male breast cancer in BRCA1 and BRCA2 mutation carriers: pathology data from the Consortium of Investigators of Modifiers of BRCA1/2. Issue 1 (December 2016) - Silvestri, Valentina; Barrowdale, Daniel; Mulligan, Anna; Neuhausen, Susan; Fox, Stephen; Karlan, Beth; Mitchell, Gillian; James, Paul; Thull, Darcy; Zorn, Kristin; Carter, Natalie; Nathanson, Katherine; et al.
Abstract Background BRCA1 and, more commonly, BRCA2 mutations are associated with increased risk of male breast cancer (MBC). However, only a paucity of data exists on the pathology of breast cancers (BCs) in men withBRCA1/2 mutations. Using the largest available dataset, we determined whether MBCs arising inBRCA1/2 mutation carriers display specific pathologic features and whether these features differ from those ofBRCA1/2 female BCs (FBCs). Methods We characterised the pathologic features of 419BRCA1/2 MBCs and, using logistic regression analysis, contrasted those with data from 9675BRCA1/2 FBCs and with population-based data from 6351 MBCs in the Surveillance, Epidemiology, and End Results (SEER) database. Results AmongBRCA2 MBCs, grade significantly decreased with increasing age at diagnosis (P = 0.005). Compared withBRCA2 FBCs, BRCA2 MBCs were of significantly higher stage (P for trend = 2 × 10−5 ) and higher grade (P for trend = 0.005) and were more likely to be oestrogen receptor–positive [odds ratio (OR) 10.59; 95 % confidence interval (CI) 5.15–21.80] and progesterone receptor–positive (OR 5.04; 95 % CI 3.17–8.04). With the exception of grade, similar patterns of associations emerged when we comparedBRCA1 MBCs and FBCs.BRCA2 MBCs also presented with higher grade than MBCs from the SEER database (P for trend = 4 × 10−12 ). Conclusions On the basis of the largest series analysed to date, our results show thatBRCA1 /2 MBCs display distinct pathologic characteristics compared withBRCA1 /2 FBCs, and we identified a specificBRCA2- associated MBC phenotype characterised by a variable suggesting greater biological aggressiveness (i.e., high histologic grade). These findings could lead to the development of gender-specific risk prediction models and guide clinical strategies appropriate for MBC management.